Evaluasi Muka Air Banjir pada Saluran Ranca Mekar akibat Pengembangan Kawasan Rumah Ibadah di Rancasari - Wijaya, Tasya; Wijaya, Obaja Triputera; Wimordi, Calvin (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2025)
Uncontrolled land-use changes are a significant factor contributing to flooding, particularly in urban areas. A plot of land in the city of Bandung is planned to be developed into a place of worship. Due to the existing topographic conditions and future planning by the local government, a drainage channel will be constructed to convey runoff from the religious facility area and the adjacent western area to the Ranca Mekar drainage channel. This study examines the impact of runoff from these two areas on the flood water level in the Ranca Mekar drainage channel. Based on the analysis, the runoff from these areas increases the flood water level (MAB) in the Ranca Mekar channel by 20-25 cm for both 2-year and 10-year return periods. This increase in flood water level is exacerbated by blockages in segment J10, caused by channel narrowing and an upward slope. Additionally, sedimentation issues along the channel reduce its capacity. The study also evaluates three alternative solutions to address these problems. The results show that reducing the slope of the channel bed in segments J10-J12 can lower the flood water level by 11 cm, whereas widening the channel dimensions in segment J10 is less effective, reducing the water depth by only 5 cm. A combination of both alternatives results in a 12 cm reduction in flood water level in segment J10 for both the 2-year and 10-year return periods. Although some alternative solutions have been effective in reducing the flood water level, further studies are required to evaluate runoff management strategies in both the religious facility gereja area and the western region. Potential measures include the implementation of retention ponds, infiltration wells, and other mitigation approaches.